Biological safety assessment of dissolved aluminum ions in coastal seawater: acute toxicity effects on Pacific whiteleg shrimp (Litopenaeus vannamei) Post-larvae - Pei-Hsuan Wu; Yen-Kung Hsieh; Tsang-Hsieh Hung; Wei-Shan Chou; Ya-Rung Wu; Ping Chen; Jin-Li Yu; Chao-Kai Kang (Ecotoxicology, 2026)

Rethinking urban resettlement housing: A production of space perspective on Shanghai’s community edible landscapes - Zhi-Wei Zheng; Rung-Jiun Chou; Yue Qin (Landscape and Urban Planning, 2025)

Assessing the Relationship between Sea Turtle Strandings and Anthropogenic Impacts in Taiwan - Wei-Rung Chou; Po-Yu Wu; Tsung-Hsien Li (Journal of Marine Science and Engineering, 2023)
Data acquired from stranded sea turtles can provide awareness of human activities that adversely affect sea turtle populations. We assessed strandings of five sea turtle species between 2017 and 2021. This study utilizes principal component analysis (PCA) and structural equation modeling (SEM) to reveal potential causes of sea turtle strandings linked to anthropogenic effects in Taiwan. Although our study did not observe a statistically significant impact of offshore wind turbines on sea turtle strandings, it did find evidence of a significant direct effect of coral colony density, heavy metals, and fishing disturbance on such strandings. For the conservation of endangered sea turtles, we recommend the incorporation of PCA and SEM in further contexts for validating anthropogenic impact assessments.

The impact and future of edible landscapes on sustainable urban development: A systematic review of the literature - Zhi-Wei Zheng; Rung-Jiun Chou (Urban Forestry & Urban Greening, 2023)

Verification of an Environmental Impact Assessment Using a Multivariate Statistical Model - Wei-Rung Chou; Hung-Yen Hsieh; Guo-Kai Hong; Fung-Chi Ko; Pei-Jie Meng; Kwee Siong Tew (Journal of Marine Science and Engineering, 2022)
Environmental impact assessment is a means of preventing and mitigating the adverse effects of economic development activities on the natural environment. It is meant to ensure that decision-makers have sufficient information to consider environmental impacts before proceeding with new projects. Despite their important role in public policy, verification of environmental impact assessments has seldom been conducted. In this study, we used principal component analysis (PCA) to identify the major sources of influence on the coastal waters adjacent to a major tourist facility (an aquarium) in southern Taiwan, followed by the construction of a structural equation model (SEM) to determine the direct and indirect effects of the abiotic factors on phytoplankton and zooplankton density and diversity. Based on the loadings of principal components 1–3, we identified that river input, suspended matter, and seasonal changes were the major factors affecting the coastal area. The SEM further suggested that phytoplankton density and diversity were affected directly by seasonal changes and suspended matter, but only indirectly by river input, owing to the latter’s effect on suspended matter. In contrast, the SEM suggested that zooplankton density and diversity were affected directly by seasonal changes, but indirectly by both river input and suspended matter owing to their effects on phytoplankton density and diversity. Q2 was the season with the highest number of visitors to the aquarium, but none of the abiotic or biotic parameters showed particular differences, implying that the variations in those parameters in the adjacent coastal waters were not related to the visitors. We suggest that PCA and SEM be used in the future in other contexts to verify environmental impact assessments.

Environmental influence on coastal phytoplankton and zooplankton diversity: a multivariate statistical model analysis - Wei-Rung Chou; Lee-Shing Fang; Wei-Hsien Wang; Kwee Siong Tew (Environmental Monitoring and Assessment, 2012)

Comparison of the decapod communities in an anthropogenic impacted lagoon and its adjacent coastal waters - Kwee Siong Tew; Wei-Rung Chou; Shih-Fung Chuang; Chun-Chung He; Jhen-Heng Liao; Lee-Shing Fang (Hydrobiologia, 2008)

Habitat and Fish Fauna Structure in a Subtropical Mountain Stream in Taiwan before and after a Catastrophic Typhoon - Kwee Siong Tew; Chiao-Chuan Han; Wei-Rung Chou; Lee-Shing Fang (Environmental Biology of Fishes, 2002)